2021
DOI: 10.1111/tmi.13688
|View full text |Cite
|
Sign up to set email alerts
|

Two‐fold increase in the HIV viral load suppression rate along with decreased incidence over six years in Ndhiwa sub‐county, Kenya

Abstract: In the last decade, progress toward HIV epidemic control has accelerated to meet the 90-90-90 targets set by the Joint United Nation Programme on HIV/AIDS (UNAIDS) for 2020: that 90% of all population living with HIV (PLHIV) know their HIV status (first 90); 90% of people aware of their HIV-positive status receive sustained antiretroviral therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The cascade of care for PLHIV in the general population in Ndhiwa 2 was; status awareness 93.4% (91.7-94.8), those linked to care 91.8% (90.0-93.4), on ART 90.4% (88.5-92.1) and those with suppressed viral load 88.3% (86.1-90.1). 16 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cascade of care for PLHIV in the general population in Ndhiwa 2 was; status awareness 93.4% (91.7-94.8), those linked to care 91.8% (90.0-93.4), on ART 90.4% (88.5-92.1) and those with suppressed viral load 88.3% (86.1-90.1). 16 …”
Section: Resultsmentioning
confidence: 99%
“…Another important finding of our study is that although we found an improvement in the cascade of care coverage and 90-90-90 UNAIDS targets between the first and second surveys more especially in Kenya, we cannot claim the same when we compare cascade of care and the 90-90-90 UNAIDS target results for individuals with advanced HIV disease with that of the general population. The general population has succeeded in achieving the targets 1 year ahead of time in both settings 16 , 17 , 33 which is why we need to put more effort into identifying those PLHIV with advanced HIV through testing, initiating them on care and ART, and ensuring that they are retained. This suboptimal coverage of the cascade of care in those with advanced HIV risks derailing the efforts of reducing HIV-related mortality and morbidity which is high among people with advanced HIV disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 3 studies locally adapted both the MDRI and the FRR as part of the analysis [ 125 , 129 , 151 ]. One study locally adapted the MDRI by weighting for local subtype distribution but assumed 0 FRR [ 133 ], and 7 studies used a published MDRI but locally estimated the FRR based on internal data [ 114 , 120 , 121 , 123 , 132 , 138 , 143 ]. One study used an FRR of 0 for the main analysis, and compared incidence results with those generated assuming an FRR of 0.39% in a sensitivity analysis [ 124 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the 51 articles describing the use of recency assays for estimation of HIV incidence, 16 (31%) [101][102][103][104][105][106][107][108][109][110][111][112][113][114][115][116] described national surveillance in the form of population-based surveys (including 10 from the US-supported Population-based HIV Impact Assessment (PHIA) surveys). Another 12 (24%) [117][118][119][120][121][122][123][124][125][126][127][128] were also population-based surveys with a representative sampling strategy, but had a community-level (subnational) focus. Most evidence related to national or subnational incidence surveillance was judged to be "very strong" (10/28), "strong" (6/28), or "moderately strong" (…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%